Effect of heat source and chemical reaction on MHD flow past a vertical plate with variable temperature - Rout, P. K.; Sahoo, S. N.; Dash, G. C. (Journal of Naval Architecture and Marine Engineering, 2016)
An analysis has been carried out to study the effect of heat source and chemical reaction on MHD flow past a vertical plate subject to a constant motion with variable temperature and concentration. The governing equations are solved by the Laplace transformation technique. The effects of various flow parameters on the flow dynamics are discussed. Findings of the present study reveal that the velocity of the fluid reduces due to the dominating effect of kinematic viscosity over molecular diffusivity in case of heavier species. Presence of heat source reduces the velocity of the flow. Presence of chemical reaction parameter decreases the concentration distribution.